Analysis of Tuberculosis Control Program (Case Detection): Literature Review - Aprilia, Reka; Nadjib, Mardiati (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2025)
To date, tuberculosis remains an infectious disease that can cause health problems in the community. In addition to increasing health risks, TB disease has an impact on the economy of a country and its sufferers. This is certainly hard for a developing country like Indonesia, which is still struggling in many ways besides TB disease. TB disease is an infectious disease caused by Mycobacterium Tuberculosis. TB case finding has the meaning of obtaining an overview through various activities including screening for suspected TB, physical and laboratory monitoring, diagnosing and categorizing the type of patient, so that treatment can be carried out as early as possible so that the patient can recover immediately and not spread to others. There are many factors that can affect the success of the tuberculosis program itself, one of which is the factor in management which includes input, process, output. Objective: This paper examines scientific evidence related to the implementation of the tuberculosis program in case detection. Methods: This article is based on a search of scientific journals conducted through online databases namely Scopus, Semantic, PubMed and Scholar published in 2020-2025. Results: In terms of TB case finding, there are many needs that must be carried out in an effort to get TB cases at health facilities. However, there are obstacles in its implementation, including lack of human resources, ineffective planning, and not optimal recording and reporting systems. Conclusion: efforts in TB case finding are highly dependent on the suitability and integration of available inputs, quality in the implementation process, and clear measurement of outputs. Therefore, efforts to improve program effectiveness require improvements in the management of inputs (such as resources and policies), optimization of processes (including more efficient detection and treatment), and continuous evaluation of outputs in TB case finding. Keywords: Tuberculosis, Case Detection, Indonesia